Trajetória na medicina UFSCar: uma narrativa reflexiva - Bueno, Lucas Ferreira de Godoy (Universidade Federal de São Carlos)
The Medical School at UFSCar is based on active learning methodologies applied to medical graduate programs, combining theory with field practice, prioritizing an early approach in healthcare services, a horizontal relationship between professors and students, and continuous reflection in the teaching-learning process. From this perspective, this course completion project aims to reflect on this author's trajectory in the Medical School at the Federal University of São Carlos (UFSCar) through the years 2020 and 2025, based on the principles of the 2007 Pedagogical Project - in effect during this author's undergraduate studies -, and complementing with the new 2025 Pedagogical Project.
Pathway in medicine at UFSCar: a reflective narrative
Keywords: Graduação; Medicina; Reflexão; CIENCIAS DA SAUDE; 3. Saúde e Bem-Estar